Asymptotically stable path following for lateral motion of an unmanned ground vehicle. (July 2015) - Shin, Jongho; Huh, Jinwook; Park, Yongwoon
Abstract: This study proposes an asymptotically stable path following controller for autonomous navigation of an unmanned ground vehicle (UGV) using vector field and robust-integral-signum error (RISE) feedback. The path following controller is divided into two parts: one part generating a heading command and another part designing a robust control. To determine the reference heading command under various uncertainties, the vector field method is employed, and then the RISE feedback controller is designed to follow the heading command. Finally, experiments are conducted on paved and unpaved roads to validate the effectiveness of the proposed method. Abstract : Highlights: This study proposes an asymptotically stable path following control algorithm for lateral motion of an unmanned ground vehicle. To follow the given reference command, the heading command is generated with the vector field method with the varying circle. The robust-integral-signum-error (RISE) feedback controller is designed with the nominal dynamic model in order to follow the heading command. The proposed algorithm is validated with two experiment composed of the collision avoidance and autonomous navigation tests.